Analytical solution and numerical simulation of advection-diffusion equation related to fumigation problem - Mohd Azuan Mohamad Nor, 1985-, author 610871 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains) - Universiti Teknologi Malaysia, 2017